(untitled) (Nigerian Journal of Technology, 2020)
Embodied energy (EE) property of building material is a great determinant of the performance of a building. The dearth of information on EE of locally sourced building materials (LSBMs) constitutes a challenge to affordable housing in Nigeria. In this paper, a review of the previous literature, unfilled gaps in those works, and future directions in embodied energy research for LSBMs is presented to evolve a Nigerian perspective. A constructive non-meta analytic methodology was adopted for the paper. This was followed by classification and comparison of snapshot literature in the embodied energy of building materials. Insightful sources of information for the study were drawn from a vast body of knowledge both documented literature and some interviews with knowledgeable personnel in the area of a built environment. From the survey, energy management opportunities were revealed, which would not have been apparent from a specific building case study alone. There are distinctions in the literature with this current paper for a Nigerian case study: none have addressed the embodied energy coefficient of materials. Also, the status of embodied energy studies, for these materials, is at a low profile and the few investigations carried out focused on life cycle operating energy of buildings. These research gaps evidently imply abundant research opportunities that await exploitation in the building industry. This paper adds to an existing body of knowledge on the use of EE index to promote and optimize the selection of LSBMs as alternative to imported building materials. We hope engineers, estate developers and architects would find it useful for making an informed decision in the design of resilient buildings using indigenous materials. http://dx.doi.org/10.4314/njt.v39i4.21